Should We Consider Them as a Threat? Antimicrobial Resistance, Virulence Potential and Genetic Diversity of Campylobacter spp. Isolated from Varsovian Dogs - Małgorzata Murawska; Monika Sypecka; Justyna Bartosik; Ewelina Kwiecień; Magdalena Rzewuska; Agnieszka Sałamaszyńska-Guz (MDPI AG, 2022)
Campylobacteriosis seems to be a growing problem worldwide. Apart from the most common sources of numerous Campylobacter species, such as poultry and other farm animals, dogs may be an underrated reservoir of this pathogen. Our goal was to establish the frequency of occurrence, antimicrobial resistance, and detection of chosen virulence factor genes in genomes of canine Campylobacter isolates. Campylobacter isolates frequency in dogs from shelters, and private origin was 13%. All of the tested virulence factor genes were found in 28 of 31 isolates. We determined high resistance levels to the ciprofloxacin and ampicillin and moderate tetracycline resistance. For C. jejuni shelter isolates, genetic diversity was also determined using PFGE. Our results indicate that dogs may be the reservoir of potentially diverse, potentially virulent, and antimicrobial-resistant Campylobacter strains.